Fiber-Wireless and Fiber-IVLLC Convergences Based on MZM-OEO-Based BLS - Chung-Yi Li; Hai-Han Lu; Chun-Yu Lin; Chien-An Chu; Bo-Rui Chen; Hung-Hsien Lin; Chang-Jen Wu (IEEE Photonics Journal)
Fiber-wireless and fiber-invisible laser light communication (IVLLC) convergences that adopt the Mach–Zehnder modulator-optoelectronic oscillator (MZM-OEO)-based broadband light source for microwave (MW)/millimeter-wave (MMW)/baseband (BB) signal transmission are proposed and demonstrated. For downlink transmission, light is optically promoted from 15- and 25-GHz radio-frequency (RF) signals to 10-Gb/s/30-GHz MW, 15-Gb/s/50-GHz MMW, 20-Gb/s/60-GHz MMW, and 25-Gb/s/100-GHz MMW data signals based on fiber-wireless and fiber-IVLLC integrations. Bit error rate (BER) performs efficiently in the 40-km single-mode fiber (SMF) and the 10-m RF/25-m optical wireless transport scenarios. For uplink transmission, downstream light is successfully intensity-modulated with a 25-Gb/s BB data stream based on fiber-IVLLC integration. BER performs efficiently in the 40-km SMF and the 100-m optical wireless transport scenario. Such a hybrid MW/MMW/BB lightwave transmission system is an attractive alternative. It is shown to be a prominent one to present advancements in integrating fiber backbone and radio-frequency (RF)/optical wireless feeder networks.